P–496 Alpha test results: Towards developing a digital prototype intervention to support parents' disclosure about donor conception in the United States. (6th August 2021) - Hershberger, P; Gallo, A; Gruss, V; Adlam, K; Driessnack, M; Grotevant, H D; Klock, S C; Pasch, L
Abstract: Study question: The objective of the study was to determine the usability, comprehensibility, and acceptability of a digital, decision-support aid prototype supporting parental disclosure of donor conception. Summary answer: This mixed methods design maximized participant feedback about the digital, decision-support aid prototype yielding rich insight about the prototype while minimizing participant and investigator burden. What is known already: Although a paradigm shift is underway to remove the secrecy that has historically shrouded the practice of gamete donation, little is known about best practices that can support parents in disclosing the conceptional origins to their children. To address this gap, we created a decision-support aid prototype to facilitate parental disclosure post-treatment. In doing so, we followed the International Patient Decision Aid Standards Collaboration for developing decision-support aids, which recommends that Alpha testing (i.e., usability, comprehensibility, and acceptability) be completed to improve the quality of newly created decision-support interventions prior to Beta (i.e., real world) testing. Study design, size, duration: A mixed-methods, triangulation design was used. Participants/materials, setting, methods: Sixteen participants were purposefully selected based on desired characteristics and the needs of the study. Participants were asked to: (1) follow investigator prepared instructions for accessing the digital, decision-support aid; (2) complete a quantitative rating form about each slide within the decision-support aid prototype; and (3) participate in a qualitative, cognitive interview or focus group. Descriptive statistics and qualitative content analysis guided the iterative analysis. Main results and the role of chance: The sample was composed of 10 parents that used donated sperm (n = 3), oocytes (n = 4), or embryos (n = 2) to conceive children and 8 clinicians; 2 participants were both donor recipient parents and clinicians. The interviews (n = 14) and one focus group (2 participants) ranged in length from 25 to 70 minutes (M = 47 minutes). Usability: Participants suggested refining the instructions for accessing the decision-support aid and upgrading the technology used to deliver the content. Common concerns were the inconsistent volume of the audio recordings and a need for higher quality images. Comprehensibility: Feedback obtained from the participants' rating forms and in the interviews and focus group were consistently high about the ability to understand the content and the scope of the information presented. Acceptability: Participants noted the aid would resonate with parents. They recommended shortening the length of the aid, changing specific wording, modifying some of the video content, refining specific content for individual slides and the four modules. Unintended recommendations about how the aid might be used to provide clinician education or in international research were also reported. Limitations, reasons for caution: Alpha testing is not designed to obtain all possible technological or content issues. Rather, it is a useful and recommended step in intervention development to mitigate existing technological bugs and key content issues prior to implementation of Beta testing of a decision-support aid. Wider implications of the findings: Other investigators that develop digital decision-support aids may consider the use of both quantitative and qualitative data collection methods during Alpha testing to refine digital interventions efficiently. The use of mixed methods not only captures rich and insightful feedback but also minimizes the burden on participants and investigators. Trial registration number: Not applicable